2014
DOI: 10.3109/0284186x.2013.871387
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced lung injury after concurrent neoadjuvant chemoradiotherapy for locally advanced breast cancer

Abstract: (2014) Radiation-induced lung injury after concurrent neoadjuvant chemoradiotherapy for locally advanced breast cancer, Acta Oncologica, 53:5, 697-701,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…Another clinical trial studied AC with paclitaxel concurrent chemoradiotherapy and showed no serious adverse reactions during the 5-year follow-up. [ 26 ] On the other hand, Chow et al [ 27 ] used FEC sequential weekly paclitaxel concurrent neoadjuvant chemoradiotherapy, but 8 patients showed grade 3 radiation pneumonitis and 1 died from respiratory distress syndrome. Thus, the dose intensity of paclitaxel may influence adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Another clinical trial studied AC with paclitaxel concurrent chemoradiotherapy and showed no serious adverse reactions during the 5-year follow-up. [ 26 ] On the other hand, Chow et al [ 27 ] used FEC sequential weekly paclitaxel concurrent neoadjuvant chemoradiotherapy, but 8 patients showed grade 3 radiation pneumonitis and 1 died from respiratory distress syndrome. Thus, the dose intensity of paclitaxel may influence adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Novel approaches, including radiotherapy, are needed to increase the pCR rate for LABC. Combined neoadjuvant chemoradiotherapy has been studied including neoadjuvant highdose rate brachytherapy (BRT) (13,14), but these modalities are difficult to organize and deliver effectively in the neoadjuvant setting and notably in some cases have resulted in acute radiation-induced side effects (15).…”
mentioning
confidence: 99%
“…The goal of the Mandilaras publication 1 was to entice readers to rethink the standard paradigm: neoadjuvant chemotherapy with or without biologic therapies, surgery, adjuvant radiation, and hormone therapy. They proposed making every attempt to improve locoregional response by exploiting treatments used in other disease sites such as radiosensitization through concurrent neoadjuvant chemotherapy and radiation, which is increasingly being evaluated 6,7 .…”
mentioning
confidence: 99%